Effects of ultraviolet irradiation with a LED device on bone metabolism associated with vitamin D deficiency in senescence-accelerated mouse P6. Issue 2 (February 2020) - Morita, Daigo; Higuchi, Yoshitoshi; Makida, Kazuya; Seki, Taisuke; Ikuta, Kunihiro; Ishiguro, Naoki; Nishida, Yoshihiro
Abstract: Aims: This study investigated effects of narrow-range ultraviolet irradiation (UVR) by a new UV–LED device on vitamin D supply and changes of bone in senescence-accelerated mouse P6 (SAMP6) with vitamin D deficiency. Main methods: We used female SAMP6 mice as a senile osteoporotic model. We set a total of 3 groups (n = 4 per group); D-UVR+ group (vitamin D deficient–dietary and UVR), D- (vitamin D deficient–dietary), and D+ groups (vitamin D contained–dietary). Mice in the D-UVR + group were UV–irradiated (305nm) with 1 kJ/m 2 twice a week for 12 weeks from 20 to 32 weeks of age. Serum 25(OH)D, 1, 25(OH)2 D, and micro–computed tomography (CT) were assessed over time. Mechanical test, and histological assay were performed for femurs removed at 32 weeks of age. Key findings: UVR increased both serum 25(OH)D and 1, 25(OH)2 D levels at 4 and 8 weeks–UVR in the D-UVR+ group compared with that in the D- group ( P < 0.05, respectively). Relative levels of trabecular bone mineral density in micro–CT were higher in the D-UVR+ group than in the D- group at 8 weeks–UVR ( P = 0.048). The ultimate load was significantly higher in the D-UVR+ group than in the D- group ( P = 0.036). In histological assay, fewer osteoclasts and less immature bone (/mature bone) could be observed in the D-UVR+ group than in the D- group, significantly. Significance: UVR may have possibility to improve bone metabolism associated with vitamin D deficiency in SAMP6 mice. Abstract : Physiology; Endocrinology; Musculoskeletal system; Pathology; Metabolism; Osteoporosis; Vitamin D; LED; Bone mineral density